Normative Tensions: European Sanction vs. ASEAN’s Non-Interference in the Case of Myanmar - Robertua, Verdinand (Program Studi Hubungan Internasional, UMY, 2014)
This article attempted to explain the relevancy of European sanction policy and ASEAN’s constructive engagement on Myanmar. In many case, normative power Europe theory which is pioneered by Ian Manners, has been an effective tool to explain the EU’s sanction policy. In this article, it will emphasize Thomas Diez’s postulation of the reflexivity of the EU’s identity as the main aspect of NPE. Consequently, it will elaborate on how EU’s identity is constructed against ASEAN who adopted constructive engagement. However, recent change in Myanmar has provoked the EU to postpone their sanction. It is puzzling because many reports from International Non-Government Organizations show that the reform in Myanmar is weak and unsustainable. ASEAN emerged as important partner for Myanmar in driving democratization and human rights regime construction in Myanmar.